300 IR HDM tablet: a sublingual immunotherapy tablet for the treatment of house dust mite-associated allergic rhinitis. (1st November 2016) - Demoly, Pascal; Okamoto, Yoshitaka; Yang, William H.; Devillier, Philippe; Bergmann, Karl-Christian
ABSTRACT: Introduction : The once-daily 300 index of reactivity (IR) house dust mite (HDM) tablet (Actair®; Stallergenes Greer, Antony, France/Shionogi & Co. Ltd., Osaka, Japan) is the first sublingual immunotherapy (SLIT) tablet to be approved for the treatment of HDM-induced allergic rhinitis. Areas covered : This drug profile reviews the current body of evidence on the efficacy, safety and tolerability of the 300 IR HDM tablet, its pharmacodynamics, and its role in clinical practice. Expert commentary : Data from its clinical development program demonstrate favorable efficacy and safety in adults and adolescents with HDM-induced allergic rhinitis, irrespective of mono- or polysensitization status, or the presence of comorbid mild asthma. The 300 IR HDM tablet is effective from as early as 2 months after treatment initiation, providing allergic symptom control and a reduction in the need for symptomatic medication, while improving health-related quality of life. Clinical efficacy is maintained for 1 year after treatment is stopped.